2021
DOI: 10.1177/00185787211032360
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Pharmacy Services During COVID-19: Pharmacists and Pharmacy Extenders Filling the Gaps Through Telehealth Services

Abstract: Purpose: The Coronavirus 2019 (COVID-19) pandemic created a significant disruption in healthcare. In our health-system located in New York City, the provision of care in the ambulatory care setting moved to a remote model virtually overnight. We describe interventions made during the pandemic to transform ambulatory care pharmacy through expansion of telehealth services. Summary: In March of 2020, the closure of primary care clinics and provider appointment cancellations due to inpatient redeployment created a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Prior to the COVID-19 pandemic, telehealth was already being used for patients with inflexible schedules who were unable to attend in-person appointments with their healthcare provider. However, there has been a surge in telehealth implementation during the past two years during the pandemic [ 37 , 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the COVID-19 pandemic, telehealth was already being used for patients with inflexible schedules who were unable to attend in-person appointments with their healthcare provider. However, there has been a surge in telehealth implementation during the past two years during the pandemic [ 37 , 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are various benefits of telehealth to both the patients and providers such as increased access to care, flexible scheduling, decreased transportation costs, and lower cancellation rates [ 39 ]. Education and training programs that incorporate resources on telemedicine and remote patient care would be helpful in improving confidence for pharmacists during their assessments [ 37 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors cast a vision for the evolving role of pharmacists to not only include practice expansion but also the incorporation of telepharmacy into standard workflow. 8,9 The use of virtual visits has been shown to be important in multiple health care settings as well as multiple areas of pharmacy practice, including both inpatient and outpatient services. 6 The Association of Health System Pharmacists (ASHP) issued a position statement in 2022 regarding telehealth pharmacy services, supporting its use to expand pharmacy access, enhance patient safety, and improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The authors cast a vision for the evolving role of pharmacists to not only include practice expansion but also the incorporation of telepharmacy into standard workflow. 8,9…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported an improvement in the quality use of medicines with the involvement of pharmacists in patient treatment. 5 , 6 , 7 , 8 , 9 , 10 The implementation of pharmaceutical services is a complex process that needs to be monitored and evaluated to ensure that the service is provided with consistent quality. 11 , 12 In recent decades, assessing the quality of service, mainly involving clinical areas, has become increasingly important to providers, regulators, and purchasers of care.…”
Section: Introductionmentioning
confidence: 99%